2002
DOI: 10.1002/env.548
|View full text |Cite
|
Sign up to set email alerts
|

Statistical verification of the Chesapeake Bay benthic index of biotic integrity

Abstract: SUMMARYThe benthic index of biotic integrity (B-IBI) developed for the Chesapeake Bay was statistically verified using simulations and a suite of multivariate statistical techniques. The B-IBI uses a simple scoring system for benthic community metrics to assess benthic community health and to infer environmental quality of benthic habitats in the Bay. Overall, the B-IBI was verified as being sensitive, stable, robust and statistically sound. Classification effectiveness of the B-IBI increased with salinity, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…The results of Alden et al (2002) indicated that the B-IBI is sensitive, stable, robust, and statistically sound. New sets of metric and threshold combinations for the tidal freshwater and oligohaline habitats were also developed in Alden et al (2002) with a larger dataset than was available to Weisberg et al (1997) for these two habitats. The present document includes the latest updates and the necessary information to calculate the Chesapeake Bay B-IBI.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The results of Alden et al (2002) indicated that the B-IBI is sensitive, stable, robust, and statistically sound. New sets of metric and threshold combinations for the tidal freshwater and oligohaline habitats were also developed in Alden et al (2002) with a larger dataset than was available to Weisberg et al (1997) for these two habitats. The present document includes the latest updates and the necessary information to calculate the Chesapeake Bay B-IBI.…”
Section: Introductionmentioning
confidence: 91%
“…Metrics for these two last habitats were developed in Alden et al (2002). The metric selection process was based on Mann-Whitney U tests for differences in means between the reference and the degraded sites of the index development data sets, and on consistency with ecological principles (Weisberg et al 1997).…”
Section: Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the possible reasons for the observed lack of sensitivity and robustness may be the chosen tested metrics. According to Alden et al (2002), four metric groups proposed by Weisberg et al (1997) proved to be significantly important to distinguish degraded from reference sites (diversity, productivity, species composition, and trophic composition). Nonetheless, for this particular case three submetrics seem to be the most important: pollution indicative taxa, pollution sensitive taxa, and diversity.…”
Section: Benthic Index Of Biotic Integritymentioning
confidence: 99%